2020
DOI: 10.21203/rs.2.20153/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Increased resistance of a methicillin-resistant Staphylococcus aureus Δagr mutant with modified control in fatty acid metabolism

Abstract: Methicillin-resistant Staphylococcus aureus (MRSA) strains are distinct from general Staphylococcus strains with respect to the composition of the membrane, ability to form a thicker biofilm, and, importantly, ability to modify the target of antibiotics to evade their activity. The agr gene is an accessory global regulator of gram-positive bacteria that governs virulence or resistant mechanisms and therefore an important target for the control of resistant strains. However, the mechanism by which agr impacts … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(16 citation statements)
references
References 16 publications
1
15
0
Order By: Relevance
“…In a previous study, we found that palmitic acid, which is the most common saturated fatty acid found in animals, plants, and microorganisms, as well as a component in soap, was capable of inhibiting biofilm formation of community-associated MRSA (CA-MRSA) LAC and its Δ agr mutant, which has a higher oxacillin minimum inhibitory concentration (MIC) (>200 μg/mL) [ 9 ]. Concomitant treatment with palmitic acid and oxacillin led to a dramatic increase in the efficacy of oxacillin.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…In a previous study, we found that palmitic acid, which is the most common saturated fatty acid found in animals, plants, and microorganisms, as well as a component in soap, was capable of inhibiting biofilm formation of community-associated MRSA (CA-MRSA) LAC and its Δ agr mutant, which has a higher oxacillin minimum inhibitory concentration (MIC) (>200 μg/mL) [ 9 ]. Concomitant treatment with palmitic acid and oxacillin led to a dramatic increase in the efficacy of oxacillin.…”
Section: Resultsmentioning
confidence: 99%
“…As a possible solution, drug combination is considered a simple method to avoid the complex resistance mechanism of S. aureus [ 8 ]. This is because multiple antibacterial agents, such as antibiotics, free fatty acids, flavonoids, and surfactants, can exert synergistic effects arising from the complex activities of their combinations [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations